2016
DOI: 10.1097/ta.0000000000000949
|View full text |Cite
|
Sign up to set email alerts
|

Multicenter evaluation of temporary intravascular shunt use in vascular trauma

Abstract: Therapeutic study, level V.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
65
0
13

Year Published

2017
2017
2021
2021

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 99 publications
(79 citation statements)
references
References 14 publications
1
65
0
13
Order By: Relevance
“…A query of the NTDB over a 5-year period revealed that only 6 centers used more than 5 shunts during this period; only 3 used more than 10 (6). The diverse nature of this population was highlighted when the NTDB revealed that 64% of vascular injuries were blunt traumas in contrast to earlier and recent studies indicating a 62–71% incidence of penetrating injuries (3, 18). This variability showcases the inherent selection bias with single center studies depending on the regional characteristics of an institution.…”
Section: Vascular Shunts In Civilian Traumamentioning
confidence: 82%
See 4 more Smart Citations
“…A query of the NTDB over a 5-year period revealed that only 6 centers used more than 5 shunts during this period; only 3 used more than 10 (6). The diverse nature of this population was highlighted when the NTDB revealed that 64% of vascular injuries were blunt traumas in contrast to earlier and recent studies indicating a 62–71% incidence of penetrating injuries (3, 18). This variability showcases the inherent selection bias with single center studies depending on the regional characteristics of an institution.…”
Section: Vascular Shunts In Civilian Traumamentioning
confidence: 82%
“…A recent analysis of the NTDB demonstrated that 74% of vascular shunts are placed in “blunt traumas associated with extensive orthopedic and/or soft tissue injury” compared to 1% in military registries (6, 16). The incidence of shunt use in civilian vascular trauma is also lower and ranges between 3 and 9% (3, 18). A query of the NTDB over a 5-year period revealed that only 6 centers used more than 5 shunts during this period; only 3 used more than 10 (6).…”
Section: Vascular Shunts In Civilian Traumamentioning
confidence: 99%
See 3 more Smart Citations